Appendiceal Neuroendocrine Tumor Is a Rare Cause of Ectopic Adrenocorticotropic Hormone Syndrome With Cyclic Hypercortisolism: A Case Report and Literature Review - Zhao, Yu Xing; Ma, Wan Lu; Jiang, Yan; Zhang, Guan Nan; Wang, Lin Jie; Gong, Feng Ying; Zhu, Hui Juan; Lu, Lin (Frontiers in Endocrinology, 2022)
Objective: Ectopic ACTH syndrome (EAS) is a condition of hypercortisolism caused by nonpituitary tumors secreting ACTH. Appendiceal neuroendocrine tumor as a rare cause of ectopic ACTH syndrome was reported few. We aimed to report a patient diagnosed of EAS caused by appendiceal neuroendocrine tumor and summarized characteristics of these similar cases reported before. Case report and literature review: we reported a case with Cushing's syndrome who was misdiagnosed as pituitary ACTH adenoma at first and accepted sella exploration. Serum and urinary cortisol decreased, symptoms relieved in following 4 months after surgery, but recurred 6 months after surgery. Abnormal rhythm of plasma cortisol and ACTH which presented periodic secretion and seemingly rising significantly after food intake. EAS was diagnosed according to inferior petrosal sinus sampling (IPSS). Appendiceal mass was identified by 68Ga-DOTA-Tyr3-octreotate (DOTATATE)-PET-CT and removed. Pathological result was consistent with appendiceal neuroendocrine tumor with ACTH (+). Literature review demonstrated 7 cases diagnosed of EAS caused by appendiceal neuroendocrine tumor with similarities and differences Conclusion: The diagnosis of ectopic-ACTH-producing tumor caused by appendiceal neuroendocrine tumor can be a challenging procedure. Periodic ACTH and cortisol secretion may lead to missed diagnosis and misdiagnosis. IPSS is crucial in the diagnosis of EAS and 68Ga-DOTATATE-PET-CT play an important role in identification of lesions.